تمثّل الموروث الثقافي في رواية خط رمل لـ: هاجر قويدري - بالصحراوي بثينة; لبــــوز هـــــــــــبة; جباس شيـــماء (University of El-Oued جامعة الوادي, 2025)
⦁ الملخص: تناولت الدراسة تمثّل الموروث الثقافي في رواية {خط رمل} لهاجر قويدري، مركزةً على استحضار التراث الشعبي والديني والتاريخي في بناء الشخصيات والأحداث، خاصة فيما يتعلق بالمرأة. اعتمدت الدراسة منهجًا سيميائيًا، وقسمت إلى مدخل مفاهيمي وثلاثة فصول تناولت العتبات النصية، والتراث التاريخي والديني، والتراث الشعبي والأدبي. خلصت الدراسة إلى نجاح الرواية في توظيف الموروث لخلق رؤية سردية تمزج الماضي والحاضر، عاكسة الصراع من أجل الهوية والانتماء. Abstract: The study examines the representation of cultural heritage in Hajar kouidri’s novel Line of Sand, focusing on the invocation of folk, religious, and historical heritage in constructing characters and events, particularly in relation to women. Adopting a semiotic approach, the study is divided into a conceptual introduction and three chapters addressing textual thresholds, historical and religious heritage, and folk and literary heritage. The study concludes that the novel successfully employs heritage to create a narrative vision that blends past and present, reflecting the struggle for identity and belonging.
مذكرة .ماستر . أدب حديث ومعاصر. 2025
Keywords: التمثّل; الموروث الثقافي; Representation